Life imprisonment and human rights - Zyl Smit, Dirk van; Appleton, Catherine (Oñati international series in law and society, 2016)
Introduction / Dirk van Zyl Smit, Catherine Appleton and Georgie Benford -- The impact of life imprisonment on criminal justice reform in the United States / Marc Mauer and Ashley Nellis -- Life imprisonment in Latin America / Beatriz López Lorca -- Life without parole in Australia : current practices, juveniles and retrospective sentencing / Kate Fitz-Gibbon -- Life imprisonment and human rights in Uganda / Jamil Ddamulira Mujuzi -- A new form of life imprisonment for India? / Madhurima Dhanuka -- An administrative procedure for life prisoners : law and practice of royal pardon in the Netherlands / Wiene van Hattum and Sonja Meijer -- Constitutionalizing life imprisonment without parole : the case of Hungary / Miklós Lévay -- A right to hope? : life imprisonment in France / Marion Vannier -- The paradox of reform : life imprisonment in England and Wales / Catherine Appleton and Dirk van Zyl Smit -- Life imprisonment in Belgium : current human rights challenges / Sonja Snacken, Ineke Casier, Caroline Devynck and Diete Humblet -- Confusingly compliant with the European Convention on Human Rights : the release of life sentence prisoners in Ireland / Diarmuid Griffin and Ian O'Donnell -- Punishment in Portuguese criminal law : a penal system without life imprisonment / Inês Horta Pinto -- The abolition of life imprisonment in Brazil and its contradictions / Giovanna Frisso -- Long-term imprisonment in Latin America / Francisco Javier de León Villalba -- Life and long-term imprisonment in the countries of the former Yugoslavia / Filip Vojta -- The right to hope for lifers : an analysis of court judgments and practice in Poland / Maria Ejchart-Dubois, Maria Nielaczna and Aneta Wilkowska-Plóciennik -- Long-term and life imprisonment in Spain : release procedures and terrorism / Jon-Mirena Landa Gorostiza -- Constitutional limits on life imprisonment and post-sentence preventive detention in Germany / Axel Dessecker -- Life without parole for preventive reasons : lifelong post-sentence detention in Switzerland / Anna Coninx -- Life imprisonment and related institutions in the nordic countries / Tapio Lappi-Seppälä